Community Empowerment Based on Local Potentials Through the Creation of “Cassava Nugget” Products in Dukuh Binangun, Werdi Village, Paninggaran District - Rizqi Toyibah; Happy Sista Devy; M. Sultan Mubarok; Ade Dedi Rohayana; Ali Muhtarom; Tamamudin; Nia Marotina; Farah Fadillah Syaufii; Hendri Hermawan Adinugraha (International Journal Of Community Service, 2021)
The problems studied in this study are how the process of potential-based community empowerment through processing of cassava nugget product creations and how the results of community empowerment based on local potential through processing of cassava nugget product creations in Hamlet Binangun, Werdi village, Paninggaran district. The objectives of this study include (1) to determine the process of community empowerment based on local potential through the processing of cassava nugget product creations in Binangun hamlet, Werdi village, Paninggaran sub-district (2) to find out the results of community empowerment activities based on local potential through the processing of cassava nugget product creations in Binangun village hamlet. Werdi, Paninggaran sub-district. This service method uses a descriptive qualitative approach. The results of research from community empowerment activities based on local potential through the processing of cassava nugget product creations are fostering an entrepreneurial spirit, utilizing existing natural potential, increasing skills by creating products that have selling value, and increasing family income or income.